Excavations of the Arab Expedition at Sār el-Jisr - Ibrahim, Moawiyah
Mu’?wiyah ’Ibr?h?m; ?afriyy?t al-bi’?ah al-’arabiyyah f? mauqi’ S?r al-?isr, 1977-1979, al-Ba?rain; Ministry of Information. State of Bahrain; wiz?rah al-’i ’l?m li-daulah al-Ba?rain; English text; Arabic text.